2014
DOI: 10.3389/fchem.2014.00043
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation stability of biodiesel fuels and blends using the Rancimat and PetroOXY methods. Effect of 4-allyl-2,6-dimethoxyphenol and catechol as biodiesel additives on oxidation stability

Abstract: In the present work, several fatty acid methyl esters (FAME) have been synthesized from various fatty acid feedstocks: used frying olive oil, pork fat, soybean, rapeseed, sunflower, and coconut. The oxidation stabilities of the biodiesel samples and of several blends have been measured simultaneously by both the Rancimat method, accepted by EN14112 standard, and the PetroOXY method, prEN16091 standard, with the aim of finding a correlation between both methodologies. Other biodiesel properties such as composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 34 publications
1
33
2
1
Order By: Relevance
“…However, after adding 3 C the test reported 6 C, which is higher than the cloud point. Unlike the trends reported from previous studies on biodiesels without antioxidants, where the reported coefficient of determinations are r 2 = 0.915 (Botella et al, 2014) and r 2 = 0.959 (Soriano et al, 2012), a weak correlation between the two standard test methods for oxidative stability was observed in the present work. These results are shown in Fig.…”
Section: High Vacuum Distilled Biodiesel Propertiescontrasting
confidence: 97%
See 1 more Smart Citation
“…However, after adding 3 C the test reported 6 C, which is higher than the cloud point. Unlike the trends reported from previous studies on biodiesels without antioxidants, where the reported coefficient of determinations are r 2 = 0.915 (Botella et al, 2014) and r 2 = 0.959 (Soriano et al, 2012), a weak correlation between the two standard test methods for oxidative stability was observed in the present work. These results are shown in Fig.…”
Section: High Vacuum Distilled Biodiesel Propertiescontrasting
confidence: 97%
“…Here, the induction period is the time it takes for the vessel pressure decrease by 10% from the measured maximum pressure of the vessel. Even though the approach is different, studies have reported good correlation between induction periods of biodiesel and biodiesel blends measured by following DIN EN 14112 and RSSOT methods (Botella et al, 2014;Soriano et al, 2012). Since induction periods obtained by RSSOT can be used to describe biodiesel oxidation and volatile components are anticipated to remain in solution at high-pressure conditions, it was hypothesized that RSSOT could be utilized to study the mechanism of biodiesel oxidation treated with antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…The adoption of B20 biodiesel by the USAF, however, correlated with an increase in reports of "bad fuel, " or fouling due to visible particulates in the fuel and clogged filters at dispensers. We hypothesized that the reported fouling was microbiological in origin, rather than from the abiotic production of waxes in fuel that was suspected by fuel operators and reported previously (Tang et al, 2008;Botella et al, 2014). Both fuel fouling and MIC have the potential to impact the operation of B20 biodiesel storage and distribution systems.…”
Section: Introductionmentioning
confidence: 90%
“…However, the slightly marginal trend of increase of the RI during storage reflects the maintenance of the physical properties of the several biodiesels, which is confirmed by the oxidative stability attained following addition of curcumin to all biofuels, in clear agreement with results published elsewhere. [3] Evaluation of the antimicrobial properties of biodiesels added with curcumin Biodiesels added with curcumin maintained a harsh environment that prevented microbial growth, which was confirmed by the screening of biodiesels for viable microbial cells throughout all storage timeframe, but all produced negative results (see Table 3 and Figure 6). Addition of water to biodiesel, coupled to the prevailing carbon sources in such a medium, would allow ubiquitous microorganisms (such as Paecilomyces variotii Bainier, a common contaminating agent in diesel fuels according to Passman [5]) to thrive in them.…”
Section: Evaluation Of the Potential Antioxidant Activity Of Curcuminmentioning
confidence: 83%
“…Considering the costs involved, sodium and potassium hydroxides promote satisfactory yields and have been widely used. [3] Microbial contamination of fuels has been reported for more than a century, since it can be spread throughout the storage and distribution systems with serious economical damages. [4,5] Although the distillation process involved in the production of biodiesel is able to sterilize the biofuel, water, dust and microorganisms can easily enter the system through the storage and transport of the fuel.…”
Section: Introductionmentioning
confidence: 99%